Prevalence of Histomonas meleagridis in Broiler Chicken in Different Parts of Mizoram, India - Patra , G.; Prasad, H.; Lalsiamthara, Jonathan; Kataria, J.L.; Malsawmkima, David; Lalrinkima, H. (International Journal of Poultry Science, 2013)
A survey was carried out to detect the overall incidence of histomoniasis in broiler birds in different parts of Mizoram, India. Out of 4000 birds examined, 40 birds were found positive for Histomonas meleagridis revealing 1% infection rate. Heterakis gallinarum was recovered from the caeca of positive birds. Gross lesions were found in caeca and liver. Microscopic examination of stained section of liver tissue revealed numerous circular amoeboid Histomonas meleagridis together with cellular infiltration. The PCR selectively amplified 209 BP of the small subunit ribosomal DNA sequence of Histomonas meleagridis.